Patterns in global value chains integration, technology and employment structures in Europe: Country and sectoral evidence - Filippo Bontadini; Rinaldo Evangelista; Valentina Meliciani; Maria Savona (European Trade Union Institute (ETUI), 2021)
This paper provides empirical evidence on the relationship between patterns of integration in global value chains (GVCs), the 'quality' of such integration in terms of technological capabilities and the structure of employment in European countries and sectors. We study employment shares in fabrication and headquarter occupations in terms of functional specialisation and employment upgrading, making two specific contributions. First, we explicitly account for pre-existing asymmetries in employment structure. Second, we account for the complex role of technology both in terms of country-industries' own initial technological intensity and that of their GVC partners. To achieve this we blend data on employment, trade in value added, patents and intangible asset stocks, for the period 2000-2014. We find that such pre-existing asymmetries are highly persistent over time with little sign of convergence in employment structure over our observed period. Furthermore GVC participation is not related, in and of itself, to changes in employment structure. However, this relationship appears to be mediated by country-industries' initial technological position. Technological leaders exhibit greater shares of employment in headquarter functions as they increase their integration in GVCs; in contrast country-industries that start off as technological laggards see further integration in GVCs alongside an increase in the share of employment in fabrication functions.
Keywords: F14; F15; O33; 330; Global Value Chains; Technology; Intangible assets; Employment; Beschäftigungsstruktur; Strukturwandel; Auslandsverlagerung; Globale Wertschöpfungskette; Hochtechnologie; Wissensintensives Unternehmen; Europa